School Principal Management in Developing Independent Learning Policy Based on Local Wisdom at MTsN 2 Bireuen - Helmi Maulana; Susi Yusrianti; Khairiani Khairiani (Yayasan Pendidikan dan Kemanusiaan Hurriah Aceh, 2025)
This study aims to analyze the management of the school principal in developing an Independent Learning policy based on local wisdom at MTsN 2 Bireuen. The focus is on the implementation of POAC management functions (Planning, Organizing, Actuating, and Controlling) in integrating Acehnese local values into the curriculum, particularly through the Pancasila Student Profile Strengthening Project (P5). This research employs a qualitative approach with a case study design. Data were collected through interviews, observations, and document analysis. The findings show that the school principal plays a strategic role in designing innovative programs rooted in local culture, mobilizing resources, and ensuring sustainable implementation through continuous evaluation. Effective management contributes to the creation of a learning ecosystem that aligns with the national education vision and local cultural values. This study recommends strengthening principals’ capacity in contextual and collaborative-based management as a key strategy for implementing the Independent Learning policy.